Relationship of Leukocyte Examination to Intra Uterine Growth Restriction (IUGR) in Pregnant Women Experiencing Anemia: Hubungan Pemeriksaan Leukosit Terhadap Intra Uterine Growth Restriction (IUGR) Pada Ibu Hamil Mengalami Anemia - Santoso, Andreas Putro Ragil; Masruroh, Nur; Filia, Sisca (Medicra (Journal of Medical Laboratory Science/Technology), 2022)
Anemia in pregnant women will often occur because of increasing gestational age, the increasing need for nutrients in the form of iron in the body which increases during the 2nd to 3rd trimester of pregnancy. Anemia has an impact of around 14-62% on pregnant women including the occurrence of Intra Uterine Growth Restriction (IUGR) which is a condition that causes fetal growth to be stunted which is characterized by the size and weight of the baby that is not appropriate during pregnancy. The next thing to worry about is the emergence of infection if the patient has IUGR. The purpose of this study was to analyze the relationship of leukocytes to IUGR in pregnant women who are anemic with the parameters measured being leukocyte levels, IUGR values in anemic patients. The study was carried out in an analytic observational manner, then samples were obtained from 24 patients. Then, the patients filled out informed consent indicating that the patient was willing to be a research sample. Furthermore, the patient's blood was taken to measure leukocyte levels and based on the KIA book, IUGR levels were measured. Based on the above, it shows that the value of the results of the Spearman correlation test is 0.085 (p> 0.05). It can be concluded that there is no relationship between leukocyte levels and IUGR values in anemic patients at IBI Surabaya Hospital.